Scanning Electron Microscopic Study on Oviduct of Goat during Follicular Phase of Estrous Cycle - Bhesaniya, Monali B; Kumar, Vishnudeo; Talekar, Shivaji H; Sharma, Anil; Sharma, Arun Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Present study was carried out to investigate the scanning electron microscopic characteristics of oviduct of goats during follicular phase of the estrous cycle. Study revealed that the presence of mucosal folds lined with ciliated and non-ciliated or secretory cells in all segments of the oviduct. The infundibulum and ampulla exhibited a dense population of ciliated cells during the follicular phase. Non-ciliated cells were few in number and interspersed between the ciliated cells. The occurrence of ciliated cells declined dramatically in the isthmus than infundibulum and ampulla.